Evaluating social work effectiveness - Cheetham, Juliet; Fuller, Roger; Mclvor, Gill.; Petch, Alison (Buckingham : Open University Press, 1992)
This book is about: Evaluation in social work; Social work effectiveness: concepts and priorities; Review of evaluative strategies; ...
Keywords: Social service; Evaluation; Scotland; Social service -- Evaluation; Evaluation research (Social action programs); Social service -- Scotland -- Case studies